Knowledge, practice and associated factors of nurses towards prevention of catheter-associated urinary tract infection in intensive care unit of public hospitals administered by Federal Government in Addis Ababa, Ethiopia: a cross-sectional institutional-based study - Tilahun Teshager; Heyria Hussien; Merahi Kefyalew; Fenta Wondimneh; Indeshaw Ketema; Sisay Habte (BMC, 2022)
Abstract Background Urinary catheterization is one of the most common procedures performed in hospitals specifically, in the intensive care units and is associated with a high risk for acquired urinary tract infections. More than 70% of acquired urinary tract infections are due to catheter use. Nurses are the primary healthcare providers responsible for inserting and maintaining urinary catheters. The data regarding nurses' knowledge, practice and associated factors towards prevention of catheter-associated urinary tract infections are limited in Ethiopia. Therefore, this study aimed to assess the knowledge, practice, and associated factors of nurses towards prevention of catheter-associated UTIs in the Intensive Care Unit (ICU) of public hospitals in Addis Ababa, Ethiopia. Methods An institutional-based descriptive cross-sectional study was conducted from March 01 to April 15, 2021, among nurses working in the ICU of public hospitals in Addis Ababa, Ethiopia. All 204 nurses working in the ICU of four public hospitals were included in the study using the census sampling method. Data were collected using a pretested self-administered semi-structured questionnaire. Data were cleaned and entered into Epi data version 4.6 and analyzed using Statistical Package for Social Sciences version 26.0. Pearson Chi-square and Fischer exact tests were performed to see the association between independent and dependent variables. The level of significance is considered at P-value less than 0.05. Results A total of 184 nurses participated in the study, making a response rate of 90.2%. The mean (±SD) age of the study participant was 29.07(±4.78). The study findings showed that more than half (63.04%) of nurses had poor knowledge and 88(47.83%) of nurses had poor practice towards prevention of catheter-associated UTIs. In this study, there was a statistically significant association between professional work experience and nurses' knowledge in preventing catheter-associated UTIs (at P-value = 0.031). Conclusion In this study, nurses' knowledge and practice towards the prevention of catheter-associated urinary tract infection was relatively poor. Professional work experience had a significant statistical association with the level of knowledge. Therefore, increasing the knowledge of nurses through appropriate educational programs and training on the preventive measures of device-associated infections was recommended to prevent catheter-associated UTIs.